Investigation and estimation of spectrophotometric values specific and molar absorbances for Losartan Potassium and Valsartan. - Tsvetkova, Dobrina Doncheva; Ivanova, Stefka Achkova (IJRDO-Journal of Applied Science, 2018)
The aim of current investigation was the investigation and estimation of spectrophotometric values specific (A1%1cm) and molar (e) absorbances for angiotensin receptor blockers Losartan Potassium and Valsartan. The following experimental results were obtained: for solutions of referense standards Losartan Potassium (lmax = 208 nm) at А > 0.2 (3.10–7 g/ml ¸ 6.75.10–7 g/ml): A1%1cm: 12113 ¸ 12778; e: 558441 ¸ 589064; for Valsartan in 99.8 % еthanol at lmax = 252 nm for А > 0.2 (6.10–6 g/ml ¸ 1.10–5 g/ml): A1%1cm : 774 ¸ 800; e: 33730 ¸ 34840. For Valsartan in mеthanol at lmax = 250 nm for А > 0.2 (3.5.10–6 g/ml ¸ 1.10–5 g/ml): A1%1cm: 480 ¸ 628; e: 20885 ¸ 27368. Specific (A1%1cm) and molar (e) absorbances for А < 0.2 were: [C] g/ml A1%1cm e 3.5.10–8 ¸ 1.10–7 13107 ¸ 16710 604252 ¸ 770348 Losartan Potassium 5.10–7 ¸ 2.10–6 877 ¸ 880 38221 ¸ 38304 Valsartan (99.8 % еthanol) 1.2.10–6 ¸ 2.5.10–6 574 ¸ 617 24997 ¸ 26875 Valsartan (mеthanol)